Uporaba polietersulfona za kapacitivni tankoplastni senzor relativne vlažnosti zraka - Požun, Karol (Kovine zlitine tehnologije, 1997)
A capacitance type relative humidity sensor utilizing polyetersulphone sensing material has been fabricated to achieve reprodicible relative measurements with long term stability even in hot and humidity conditions. The sensor showed a good performance with low hysteresis and low temperature coefficient of capacitance along with good stability with less than 3% (r.h.) shift after 1000 hours of exposure to 40°C, 90% r.h. conditions.
Keywords: polimeri; vlaga; senzorji; relativna vlažnost; polietersulfon